Effects of shapes and kinematics of hovering flapping wings on aerodynamic forces and vortex structures - Hyun Ki Kwon; Jo Won Chang (Scientific Reports, 2025)
Abstract The present study investigated the effects of wing shapes and flapping motions on the aerodynamic forces and vortex structures of insect flight. Aerodynamic force measurements and flow visualizations were performed in a water tank by cross-applying the wing shapes of bumblebee, hawkmoth, and hummingbird to their hovering flapping motions. When the three different wings were measured making the same motions, the average difference of lift-to-drag ratio was 2.7%. In the aspect ratio and wing area distribution range, where three wing shapes were distributed, aerodynamic performances were similar according to wing shape. However, the average difference of lift-to-drag ratio was 34.3% when flapping motion was differed within the same wing shape. The aerodynamic performances of three flapping motions varied significantly with changes in sweeping speed and wing rotation. The difference of average in aerodynamic efficiency was 4.9% among the three wings when making the same motion, and 43.7% when the motions were differed in the same wing. The results showed that flapping motions had significant effects on aerodynamic performance. Visualization results also showed that the vortex structure changes significantly when motions are different in the same wing shapes. These findings provide valuable data for designing flapping micro air vehicles and morphing aircraft.